Cytokines as therapeutics and targets of therapeutics - Vilček, J; Feldmann, M (2006)
Cytokine research has spawned the introduction of new therapies that have revolutionized the treatment of many important diseases. These therapeutic advances have resulted from two very different strategies. The first therapeutic strategy embodies the administration of purified, recombinant cytokines. The second relies on the administration of therapeutics that inhibit the harmful effects of upregulated, endogenous cytokines. Examples of successful cytokine therapeutics include hematopoietic growth factors (colony stimulating factors) and interferons. Prime examples of cytokine antagonists that have profoundly altered the treatment of some inflammatory disorders are agents that inhibit the effects of tumor necrosis factor (TNF). In this article, we highlight some of the studies that have been responsible for the introduction of cytokine and anti-cytokine therapies, with emphasis on the development of interferons and anti-TNF agents.